2019
DOI: 10.1038/s41598-019-50895-6
|View full text |Cite
|
Sign up to set email alerts
|

Performance of landscape composition metrics for predicting water quality in headwater catchments

Abstract: Land use is a predominant threat to the ecological integrity of streams and rivers. Understanding land use-water quality interactions is essential for the development and prioritization of management strategies and, thus, the improvement of water quality. Weighting schemes for land use have recently been employed as methods to advance the predictive power of empirical models, however, their performance has seldom been explored for various water quality parameters. In this work, multiple landscape composition m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…The performance of land cover metrics in water quality prediction, calculated for different spatial scales with even additional distance of flow accumulation scaling, was previously broadly discussed [42,45,92]. However, the presented results are not clear and unequivocal.…”
Section: Land Cover Effect On Nutrient Variabilitymentioning
confidence: 76%
See 3 more Smart Citations
“…The performance of land cover metrics in water quality prediction, calculated for different spatial scales with even additional distance of flow accumulation scaling, was previously broadly discussed [42,45,92]. However, the presented results are not clear and unequivocal.…”
Section: Land Cover Effect On Nutrient Variabilitymentioning
confidence: 76%
“…Some of the previous studies also indicated that even with the same land use percentage, landscape configuration, measured with the patch density, edge density, and mean shape index, plays an important role in organic matter and nutrient runoff from catchments [39]. However, this can be more important in larger catchments, where their area is suggested to have a significant effect on metrics performance [42].…”
Section: Land Cover Effect On Nutrient Variabilitymentioning
confidence: 97%
See 2 more Smart Citations
“…In addition to the intrinsic random nature of urban runoff quality, most of the works mentioned above have also demonstrated that many multifaceted interactions among these factors have occurred in multi-dimensions. In such conditions, conventional univariate (e.g., ANOVA) and multivariate (e.g., linear regression) statistical techniques have been widely adopted to investigate the correlation among water quality characteristics and influential factors [3,14]. However, the outcomes were often affected by several sources of statistical bias, unless all the analysis requirements (e.g., model selection criteria, parametric assumptions, and interaction terms) were rigidly tackled or fixed [9,15].…”
Section: Introductionmentioning
confidence: 99%